Perancangan Hotel Resort di Kabupaten Nias Utara dengan Tema Arsitektur Kontekstual - Rozaman Zalukhu; Ina Triesna Budiani; Aulia Muflih (Jurnal Ilmiah Teknik Sipil dan Arsitektur (JITAS), 2022)
The increasing number of tourists in North Nias Regency has encouraged the writer to plan the design of resort hotels in North Nias Regency as a place to stay for local and foreign tourists. In designing a resort hotel, the author chooses a location that has attractive potential and is easily accessible to visitors. In North Nias Regency, there are 33 interesting tourist objects consisting of beaches, mountains, caves, and waterfalls that can be selected, including for the location of the site in the design of the hotel resort. The method used in the design of hotel resorts is descriptive analysis method, namely by carrying out several stages of analysis accompanied by a study of literature that supports the theory. This analysis uses qualitative analysis, namely collecting data in the form of detailed stories or actual conditions by surveying comparative study objects related to the design, and conducting site site surveys. The design of resort hotels in North Nias uses a design approach through contextual architecture. The shape of the building can relate to the site's environment, the condition of the surrounding buildings, society, culture, and materials in the local area. The application of contextual architecture also takes the surrounding design motifs such as mass forms, patterns and ornaments.